Fitting (Tempat Lampu) Berbasis Internet of Things (IoT) Menggunakan Arduino - Sistri Indah Purnama Indah Purnama; Yance Sonatha; Humaira - (SOTVI - Society of Visual Informatics, 2021)
The use of technology in various fields can provide convenience in life, especially in electronic equipment, namely lamps. The use of lights occurs during the day and night with excessive intensity of use can lead to waste of electrical energy in the house. Therefore, it is necessary to have a tool capable of checking the condition of lights using light sensors, current sensors and voltage sensors. The lamp condition check tool applied in the house is expected to make it easier for the occupants of the house to know the information on the condition of the lights in the house when left behind and can be accessed on the website so as to minimize the use of electricity in the house.